Mechanochromic Reconfigurable Metasurfaces. Issue 21 (12th September 2019) - Karvounis, Artemios; Aspiotis, Nikolaos; Zeimpekis, Ioannis; Ou, Jun‐Yu; Huang, Chung‐Che; Hewak, Daniel; Zheludev, Nikolay I.
Abstract: The change of optical properties that some usually natural compounds or polymeric materials show upon the application of external stress is named mechanochromism. Herein, an artificial nanomechanical metasurface formed by a subwavelength nanowire array made of molybdenum disulfide, molybdenum oxide, and silicon nitride changes color upon mechanical deformation. The aforementioned deformation induces reversible changes in the optical transmission (relative transmission change of 197% at 654 nm), thus demonstrating a giant mechanochromic effect. Moreover, these types of metasurfaces can exist in two nonvolatile states presenting a difference in optical transmission of 45% at 678 nm, when they are forced to bend rapidly. The wide optical tunability that photonic nanomechanical metasurfaces, such as the one presented here, possess by design, can provide a valuable platform for mechanochromic and bistable responses across the visible and near infrared regime and form a new family of smart materials with applications in reconfigurable, multifunctional photonic filters, switches, and stress sensors. Abstract : Mechanochromic response is presented as a method to tune optical properties of photonic metasurfaces. A subwavelength array of silicon nitride/molybdenum oxide and molybdenum disulfide nanowires due to heat‐activated mechanical strain alters its optical properties drastically in the visible part of the spectrum with transmission change up to 197% and mechanically bistable response.